The interplay between spin densities and magnetic superexchange interactions: case studies of mono- and trinuclear bis(oxamato)-type complexes - Aliabadi, Azar; Büchner, Bernd; Kataev, Vladislav; Rüffer, Tobias (Beilstein Journal of Nanotechnology, 2017)
For future molecular spintronic applications the possibility to modify and tailor the magnetic properties of transition-metal complexes is very promising. One of such possibilities is given by the countless derivatization offered by carbon chemistry. They allow for altering chemical structures and, in doing so, to tune magnetic properties of molecular spin-carrying compounds. With emphasis on the interplay of the spin density distribution of mononuclear and magnetic superexchange couplings of trinuclear bis(oxamato)-type complexes we review on efforts on such magneto-structural correlations.
Keywords: bis(oxamato); bis(oxamidato); copper(II); electron nuclear double resonance; electron paramagnetic resonance; magnetic superexchange interactions; pulsed electron–electron double resonance; spin density distribution